Особенности употребления вспомагательного глагола в формах перфекта в 1-м лице единственного числа в древнерусских грамотах XIV–XVI вв. - Waraczewski, Maciej (Studia Rossica Posnaniensia, 2019)
This paper analyzes the use of perfect tense forms in a collection of Old-Russian charters: Testaments and Contractural Letters of the Russian Great and Appanage Princes of the XIV–XVI centuries. A special attention has been paid to the connection between the presence of an explicit subject and an auxiliary verb and their strict mutual dependence has been proved.